Spotlight on COVID‐19: from biology to therapy and prevention. (7th September 2020) - Zacchigna, Serena; Marcello, Alessandro; Banks, Lawrence
Abstract : In this COVID‐19 Focus Issue, we highlight a collection of recently published The FEBS Journal articles that consider the broader aspects of the COVID‐19 pandemic, ranging from the debunking of urban myths to highlighting some of the most pressing questions concerning SARS‐CoV‐2 infection, treatment, prevention and pathology. The collection comprises two review articles, six Viewpoints, two research papers and one commentary. We hope that these articles will provide readers with an informative and interesting overview that will promote further critical analysis of currently available data and observations on COVID‐19.